A bidirectional crosstalk between autophagy and TP53 determines the pace of aging. (2nd September 2020) - Sica, Valentina; Kroemer, Guido
ABSTRACT: When the orthologue of tumor suppressor protein p53 ( TP53), cep-1, is inactivated in Caenorhabditis elegans, the nematodes manifest an autophagy-dependent increase in lifespan. A recent paper by Yang et al . demonstrates that accelerated aging phenotype of autophagy-deficient mice can be reduced by the knockout (KO) of Trp53 . These findings point to a complex bidirectional crosstalk between autophagy and TP53 that has vast implications for the aging process.